Assesment of morphometric and hydrological properties of smalls watersheds in East Java Regions - Sujarwo, Mohamad Wawan; Indarto, Indarto; Wiratama, Ega; Teguh, Bobby (Jurnal Teknik Sipil, 2019)
This paper presents the identification, assessment and visualization of physical, topographic, morphometric and hydrological properties of small watersheds in East Java Regions.  About 45 small watersheds were used for the analysis.  Physical propertis i.e: soil type layers, land use, etc were obtained by cropping the GIS layers with a watershed boundary. Then the ASTER G-DEM2 was used to derive morphometric properties of the watersheds. Furthermore, hydrological properties are derived statistically by analyzing available rainfall and discharge data. Parameters were selected to represent each watersheds properties. Finally, simple correlation analyses through the selected parameters were used to interpret the relation between physical, topographical, morphometric and hydrological properties of the watersheds. The resut show that some watersheds show the similtarity in certain parameters.Artikel ini menyajikan identifikasi, penilaian dan visualisasi sifat fisik, topografi, morfometrik dan hidrologi daerah aliran sungai kecil di Wilayah Jawa Timur. Empat puluh empat (44) DAS digunakan untuk analisis. Sifat fisik (yaitu, jenis tanah dan penggunaan lahan) diperoleh dengan memotong lapisan GIS dengan batas daerah aliran sungai. Kemudian ASTER G-DEM2 digunakan untuk menurunkan sifat morfometrik daerah aliran sungai. Selain itu, sifat hidrologis diperoleh dengan menganalisis data curah hujan dan debit yang tersedia. Parameter yang dipilih adalah untuk mewakili setiap properti daerah aliran sungai. Akhirnya, korelasi sederhana antara sifat-sifat fisik, topografi, morfometrik, dan hidrologi daerah aliran sungai. Hasil penelitian menunjukkan bahwa beberapa DAS menunjukkan kesamaan dan perbedaan pada parameter morfometrik dan hidrologi.